A Self-Reference Effect on Memory for People: We Are Particularly Good at Retrieving People Named Like Us - Brédart, Serge (Frontiers in Psychology, 2016)
In the present study, it was evaluated whether one’s own name may produce a self-reference bias in memory for people. Results from Experiment 1 indicated that, in a verbal fluency task, participants recalled a greater number of known (familiar or famous) people with the same first name as their own than did paired participants, and vice versa. In the first experiment, paired participants knew each other but were not close. Experiment 2 examined whether this self-reference effect would still occur when the comparison target was a close other. This experiment showed that such a self-reference bias also occurred even when the paired persons were close (partners or very good friends). Overall the present paper describes a new naturalistic case of the self-reference effect.